Estimating fiscal multipliers in selected Asian economies - Roselle Dime; Edimon Ginting; Juzhong Zhuang (Asian Development Bank (ADB), 2021)
This paper estimates fiscal multipliers using quarterly data for a panel of nine developing Asian economies, following a vector autoregression model specification, but using local projections to extract the impulse responses. We provide evidence that the 4-quarter and 8-quarter cumulative multipliers for general government spending range between 0.73 and 0.88 in baseline estimations, in line with recently reported estimates for developed countries but larger than those for developing countries. We also find that the corresponding tax multipliers range between -0.41 and -0.62, significantly smaller than recently reported estimates for developed countries but larger than those for developing countries. These results suggest that, without the stimulus measures introduced by countries around the world since the start of the COVID-19 pandemic, the global economy would have suffered even greater output loss. This paper also shows evidence that an economy's structural and transitory characteristics can affect the size of fiscal multipliers. Economies that are less open to trade, have a lower level of debt, adopt a less flexible exchange rate, or maintain accommodative monetary policy have larger spending multipliers than those that are more open to trade, have a higher debt level, adopt a more flexible exchange rate, and maintain contractionary monetary policy. However, the business cycle appears to have little effect on the size of spending multipliers. We also find that the economies with a less flexible exchange rate have larger tax multipliers. But other structural and transitory characteristics appear to not have the expected effects on tax multipliers.
Keywords: C32; E62; H50; O53; 330; fiscal multipliers; Asian economies; VAR models; COVID-19 pandemic